Answer:
y =
(x and y intercepts under "Step-by-step explanation" section)
Explanation:
We can start by finding the vertex form and then expand it to the standard form.
The vertex form of the quadratic equation is
, where a is a constant and (h, k) is the vertex.
By plugging in 1 for a, -1 for h, and 11 for k, we have:
![y=1(x-(-1))^2+11\\y=(x+1)^2+11](https://img.qammunity.org/2023/formulas/mathematics/high-school/smcrprsem0quzcy0xgn948qmtka79krbdd.png)
Now we simply expand this vertex form to get the standard form:
![y = (x+1)^2+11\\y=(x+1)(x+1)+11\\y=x^2+x+x+1+11\\y=x^2+2x+12](https://img.qammunity.org/2023/formulas/mathematics/high-school/10g1pwir39ehdhsk6jkftcwe3cnu8y6jx5.png)
We can find the x and y-intercepts using the vertex form.
To find the x-intercept, we plug in 0 for y:
![0=(x+1)^2+11\\-11=(x+1)^2\\√(-11)=x+1;-√(11)=x+1\\ x_(intercepts):(-1+√(-11), 0); (-1-√(-11))](https://img.qammunity.org/2023/formulas/mathematics/high-school/ikhmnv2u4dtp7y8pzf2d86xf1ilwdng5el.png)
The x-intercepts are non-real answers, so the quadratic equation never intersects the x-axis.
To find the y-intercept, we plug in 0 for x:
![y=(0+1)^2+11\\y=1^2+11\\y_(intercept) =(0,12)](https://img.qammunity.org/2023/formulas/mathematics/high-school/llytnp1bg98fiv6hl4c1tl0njif88dnzgz.png)